Detection of a plant enzyme exhibiting chlorogenate-dependant caffeoyltransferase activity in methanolic extracts of arbuscular mycorrhizal tomato roots - Negrel, Jonathan (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.